Program Evaluation and Archives: "Appraising" Archival Work and Achievements - Grimard, Jacques (Archivaria, 2004)
The purpose of this article is to illustrate the potential of program evaluation for archives and to lay the foundation for the development of a research initiative on this subject. It explores two basic questions: “What is program evaluation?” and "Is the concept applicable to archives?” Based on an extensive review of the literature, it demonstrates that in archives, as elsewhere, program evaluation has to rely on a judicious mix of approaches. It also offers considerations on criteria, measurements and indicators for archival activities, products, and services. This paper concludes that archivists would find it strategically opportune to develop their knowledge and expertise on program evaluation and to explore further the theory and the potential applications of program evaluation methodologies. It suggests the development of a research initiative on program evaluation applicable to archives. RÉSUMÉ L'objectif de cet article est d'illustrer le potentiel de l'évaluation de programme pour les institutions d'archives et de poser les fondements du développement d'un projet de recherche sur le sujet. L'auteur explore deux questions essentielles: « Qu'est-ce que l'évaluation de programme ? » et « Est-ce que ce concept est applicable pour les institutions d'archives ». En se basant sur un examen approfondi de la littérature, il démontre que dans les institutions d'archives, comme ailleurs, ce genre de programme doit se fonder sur un mélange judicieux d'approches. Il offre également des réflexions sur les critères, les mesures et les indicateurs des activités, produits et services archivistiques. L'article conclut que les archivistes trouveraient opportun et stratégique de développer leurs connaissances et leur expertise sur l'évaluation de programme et d'en explorer plus avant la théorie et les applications potentielles au niveau méthodologique. Il suggère le développement d'un projet de recherche sur l'évaluation de programme applicable aux institutions d'archives.